Asaia spp., acetic acid bacteria causing the spoilage of non-alcoholic beverages - Iveta Šístková; Iveta Horsáková; Mariana Hanková; Helena Čížková (Kvasný průmysl, 2019)
After a general introduction and introduction to acetic acid bacteria, this work focuses on the genus Asaia, which causes sensory defects in non-alcoholic beverages. Asaia representatives have strong adhesive properties for materials used in the food industry, where they subsequently form biofilms and are highly resistant to chemical preservatives. After the basic characteristics of the genus Asaia and its influence on humans, the main part of the paper deals with microbial contamination of beverages by these bacteria. The paper summarizes the knowledge of the influence of packaging materials on the development of defects in beverages and the use of natural bioactive substances and plant extracts as an alternative to maintaining the microbiological stability of beverages.